2013
DOI: 10.1007/s11434-013-5728-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between indoor environmental smoke and respiratory symptoms among preschool children in Shanghai, China

Abstract: Whether indoor environmental smoke is harmful for preschool children's respiratory health in a society where female smoking is rare has not been determined. This study is part of a cross-sectional study (CCHH study-phase one in Shanghai) and investigated associations between parental smoking and incense-burning and respiratory symptoms among 4-6 year old children in Shanghai, China. A number of 13335 valid questionnaires (response rate: 85.3%) were analyzed. A number of 56.1% (as reported by a parent) of presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
(81 reference statements)
0
20
3
Order By: Relevance
“…The questionnaire was tested in a pilot study of 100 children in Chongqing in April 2010, and thereafter adjusted to improve readability. For details about questionnaire design, see articles for specific CCHH cities [58][59][60][61][62][63][64][65][66][67][68]. …”
Section: Questionnaire Design and Pilot Studymentioning
confidence: 99%
“…The questionnaire was tested in a pilot study of 100 children in Chongqing in April 2010, and thereafter adjusted to improve readability. For details about questionnaire design, see articles for specific CCHH cities [58][59][60][61][62][63][64][65][66][67][68]. …”
Section: Questionnaire Design and Pilot Studymentioning
confidence: 99%
“…Specifically, studies over the past 10 years indicate that the prevalences of asthma and allergies in China are rapidly increasing (Qu et al., ; Wong et al., ; Yangzong et al., ; Zhang et al., ; Zhao et al., ). In Shanghai, a cross‐sectional questionnaire study found that the prevalence of asthma among children had increased from 1.90% in 1990 to 10.3% in 2011 (Huang et al., ; Liu et al., ), most likely due to changed environmental exposures (Zhang et al., ), and perhaps especially exposures in the homes (Diette et al., ; von Mutius, ; Repace and Lowrey, ; Turner, ). The China, Children, Homes, Health (CCHH) project is currently studying associations between home environment and asthma and allergies in 10 cities in China (Huang et al., ; Liu et al., , ; Qu et al., ; Wang et al., ,b; Zhang et al., ,b; Zhao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Shanghai, a cross‐sectional questionnaire study found that the prevalence of asthma among children had increased from 1.90% in 1990 to 10.3% in 2011 (Huang et al., ; Liu et al., ), most likely due to changed environmental exposures (Zhang et al., ), and perhaps especially exposures in the homes (Diette et al., ; von Mutius, ; Repace and Lowrey, ; Turner, ). The China, Children, Homes, Health (CCHH) project is currently studying associations between home environment and asthma and allergies in 10 cities in China (Huang et al., ; Liu et al., , ; Qu et al., ; Wang et al., ,b; Zhang et al., ,b; Zhao et al., ). Recently, the Shanghai group of CCHH reported that early furred pet‐keeping (Huang et al., ) and parental smoking (Liu et al., ) were risk factors for asthma and allergies among preschool children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Beijing: possible protective effect of breastfeeding against asthma and allergy [18]; From Shanghai: risks associated with exposure to pets [19] and risks associated with ETS [20]; From Wuhan: risk factors in the home environment associated with asthma and rhinitis [21] and risk factors in the home environment associated with eczema [22];…”
mentioning
confidence: 99%